The Course Improvement Flowchart: A description of a tool and process for the evaluation of university teaching - Morgan, P. (Journal of University Teaching and Learning Practice, 2008)
The use of evaluation to examine and improve the quality of teaching and courses is now a component of most universities. However, despite the various methods and opportunities for evaluation, a lack of understanding of the processes, measures and value are some of the major impediments to effective evaluation. Evaluation requires an understanding of what to evaluate, how to evaluate it, how to collect and analyse the information and how to action and implement what has been learned. The aim of this paper is to describe an instrument to document not only the evaluative process, but also evaluative outcomes. The Course Improvement Flowchart (CIF) provides a template for the application of an action inquiry framework. Throughout this process, the CIF template can be used to document key recommendations emanating from multiple sources of feedback so that a proactive statement of intent or action plan for teaching and course improvement is written. The resultant improvements that may be achieved in teaching and course quality may lead to more satisfying teaching experiences, improved student outcomes and heightened professional growth as a teacher.